The Effect of an Explicit Strategy Instructional Approach for the Treatment of L2 Writing Difficulties - Tarawhiti, Nancy (Auckland University of Technology, 2016)
Writing difficulties (WDs) have been investigated to identify what they are and how they occur, but not necessarily how to address them within a specific genre (Barsturkmen & Randow, 2014; Bitchener & Barsturkmen, 2006; Casanave & Hubard, 1992; Cooley & Lewkowicz, 1995; Hinkel, 2011; Hyland, 2002; Leki, Cumming & Silva, 2008; Ong, 2011; Silva, 1990; Thompson, Morton & Storch, 2013; Zhang, 2000). Because empirical research has shown strategies can help students improve their use of the English language, strategies were considered as one way of addressing specific WDs (Chamot, 2005; Griffiths, 2008; O’Malley & Chamot, 1990; Oxford, 1986, 1990). Before investigating strategies, this thesis investigates approaches to resolving WDs and different perspectives about why WDs may occur in the expository genre. With that information, this thesis investigates the effectiveness of an explicit strategy instructional approach for addressing the identified WDs and for determining whether the knowledge gained from such an approach was retained and used appropriately after a 10-week period. This research was conducted with 70-second language (L2) students at a large University in the USA. A quasi-experimental study design was employed, including a pre-test / intervention / immediate and delayed post-test methodology to establish whether the instruction was effective. Additionally, a survey was used to investigate students’ perceived WDs in relation to their actual WDs. The first result showed that WDs related to linguistic accuracy (local WDs) were the most problematic and that these were followed by difficulties with writing appropriate propositions (global WDs) and difficulties with supporting them with appropriate examples (global WDs). The second result showed that there was no relationship between students’ perceptions of what was difficult for them and the difficulties that their writing revealed. The final result showed that the explicit strategy instruction was effective for writing appropriate propositions and for examples of propositions in the immediate post-test. The effectiveness of the explicit strategy instruction was also ‘retained’ over time for a number of students when immediate and delayed post-test texts were compared. Additionally, there were a few students who ‘improved’ in the delayed post-tests but who had not improved in the immediate post-test.
Keywords: Writing difficulties; Explicit strategy instruction; Second language writing; Strategies